2005
DOI: 10.1111/j.1365-2702.2004.01107.x
|View full text |Cite
|
Sign up to set email alerts
|

Registered Nurses’ personal rights vs. professional responsibility in caring for members of underserved and disenfranchised populations

Abstract: Registered Nurses are accountable for nursing decisions and actions regardless of personal preferences. Due to the rapidly changing healthcare system the nurse faces increasing ethical dilemmas and human rights issues. Nurses are individually accountable for caring for each patient and the right to refuse an assignment should be carefully interpreted to avoid patient abandonment. Nurses' objections can be based on moral, ethical, or religious beliefs not on personal preferences and in an emergency the nurse mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 25 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…Nurses are accountable for the care they provide, and the provision of inadequate care based on prejudice or discrimination can result in disciplinary action. [15] These points indicate further research needs to be done on teaching methods to determine the most effective way of conveying cultural information in fostering cultural competence in nursing students and ultimately among nursing graduates.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Nurses are accountable for the care they provide, and the provision of inadequate care based on prejudice or discrimination can result in disciplinary action. [15] These points indicate further research needs to be done on teaching methods to determine the most effective way of conveying cultural information in fostering cultural competence in nursing students and ultimately among nursing graduates.…”
Section: Significancementioning
confidence: 99%
“…Some studies that used this model showed its effectiveness in guiding teaching and learning methods, but there is a need for further research identifying predictors of cultural competence. [23][24][25][26][27][28][29][30][31][32][33][34][35][36] Many approaches were noted in the literature related to cultural competence in the curriculum, and are summarized as follows: the need to critically evaluate implementation and evaluation methods of cultural concepts in the curriculum, [4,9,10,12,15,17,38,39] use of a stand-alone course on culture in the curriculum, [22,30] integration of cultural concepts throughout the curriculum, [12,13,40] use of service learning projects and cultural immersion projects to increase cultural competence, [11,12,[41][42][43][44][45][46][47] lack of qualified faculty members to teach cultural concepts, [23,48] need for course material to adapt to the changing learning needs of students, [45] and international collaboration among teaching institutions to teach cultural competence. [6,35,39,49] While the above note...…”
Section: Introductionmentioning
confidence: 99%
“…The book Leaky Bodies and Boundaries by Margrit Shildrick (1994) argues that bodies of women have been continually marginalized and respected in a vastly different way from men (Shildrick, 1997). Discrimination can be based on any number of things including the disenfranchised groups with conditions that delineate them as different from the popular mainstream, and this marginalization in itself can cause anxiety, stress, and illness just within the physiologic effects of membership (Maze, 2005). The woman affected by PCOS is marginalized by the existence of body hair.…”
Section: Nursing and Kristeva's Abjectionmentioning
confidence: 97%
“…The nurse who refuses care balanced carefully with the responsibility to not abandon those patients who need them so desperately. Refusal can result in the loss of licensure if the nurse is found guilty of abandoning the patient, so this decision should always be taken with great deliberation (Maze, 2005). This ability to refuse care creates a type of discrimination.…”
Section: Professional Nurse Caringmentioning
confidence: 99%
“…Reviews of the literature (Martino Maze 2005; Myhrvold 2006) have highlighted the importance of caring relationships with disenfranchised persons, although conclusions tend to be nurse‐centric rather than recognizing the power that clients have in the relationship and its enactment, and obscuring the constraints that policies can have on nursing practice (RNAO 2006). Other research has focused on the development of community‐based health clinics for people experiencing homelessness and often focuses on the need for positive attitudes and environments that foster casual nurse–client interactions (Lafuente and Lane 1995; Gerberich 2000; Gill 2000).…”
Section: Review Of the Literaturementioning
confidence: 99%